2021
DOI: 10.1177/23814683211061398
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Roles in Decision-Making Among Asian Patients With Advanced Cancer: A Multicountry Study

Abstract: Purpose. We investigated 1) perceived roles in decision-making among advanced cancer patients in 5 Asian countries 2) associations of patient characteristics with these roles, and 3) the association of perceived roles with quality of life and perceived quality of care. Methods. We surveyed 1585 patients with stage IV solid cancer. Multinomial logistic regressions were used to analyze associations of patient characteristics with decision-making roles. Multivariate regressions were used to analyze associations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Many factors can influence patient involvement in decision making, especially near EOL. Studies indicate that younger age, 2 higher education, 3 higher income, 3 and being nonminority 4 consistently predicted higher levels of involvement in decision making, while evidence on gender 5 and marital status 6 has been mixed. Cognitive difficulties could affect older individuals’ participation in decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can influence patient involvement in decision making, especially near EOL. Studies indicate that younger age, 2 higher education, 3 higher income, 3 and being nonminority 4 consistently predicted higher levels of involvement in decision making, while evidence on gender 5 and marital status 6 has been mixed. Cognitive difficulties could affect older individuals’ participation in decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been designed to help patients obtain the information they need to enable them to play an active role in their care under a more equitable partnership. Although SDM has been increasingly popular in healthcare practice in Asia [6] and Taiwan [7], barriers may still be encountered [8], and the integration of digital and online processes on a hospital-wide implementation scale has scarcely been reported. Leaders in healthcare organizations are keen to run their service more efficiently and respond to patients' needs.…”
Section: Introductionmentioning
confidence: 99%
“…These patients preferred to share decisions about cancer treatments with their family [30]. A previous study found that making decisions alone was linked to lower emotional, social, and spiritual wellbeing among Asian patients with advanced cancer, whereas making decisions jointly with doctors and family was linked to greater social and spiritual wellbeing [37]. Spending more time discussing treatment choices with family members helps patients cope with their cancer diagnosis and promotes cognitive processing, both of which may eventually reduce the patient's stress levels [38].…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%